2020
DOI: 10.1038/s41598-020-76843-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing long-term impacts of ungulate herbivory on forest-recruitment dynamics at community and species level contrasting tree densities versus maximum heights

Abstract: Herbivores are constitutive elements of most terrestrial ecosystems. Understanding effects of herbivory on ecosystem dynamics is thus a major, albeit challenging task in community ecology. Effects of mammals on plant communities are typically explored by comparing plant densities or diversity in exclosure experiments. This might over-estimate long-term herbivore effects at community levels as early life stage mortality is driven by a multitude of factors. Addressing these challenges, we established a set of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 74 publications
1
4
0
1
Order By: Relevance
“…Because of browsing, some species grow sparingly in height, become dominated by less browsing-sensitive species, and gradually disappear. This was observed for highlight species in our study (Figure 2) and supported our assumption that the browsing effect on seedling growth is a good indicator of future tree recruitment, according to [80].…”
Section: Seedling Density and Species Occurrencesupporting
confidence: 91%
“…Because of browsing, some species grow sparingly in height, become dominated by less browsing-sensitive species, and gradually disappear. This was observed for highlight species in our study (Figure 2) and supported our assumption that the browsing effect on seedling growth is a good indicator of future tree recruitment, according to [80].…”
Section: Seedling Density and Species Occurrencesupporting
confidence: 91%
“…However, the large increase in abundance over time when excluding deer and sheep to 0.44 rowans/m 2 opposed to only 0.07 rowans/m 2 in ungulate-access plots is perhaps more remarkable than shown in most previous studies. Although there are variation in plant species responses to excluding ungulates (Fortuny et al, 2020), other studies comparable in design, study period and ungulate species have typically found that exclosures exhibit around double the increase in rowan abundance over time compared to controls (Speed et al, 2013;Nopp-Mayr et al, 2020). The effect of excluding deer and sheep in our study is more equivalent to that found when excluding the most typical browser of northern ecosystems, the moose (Alces alces), from clear-cuts (Kolstad et al, 2018), a habitat that typically offers better conditions for germination of rowan than shaded old-growth forest.…”
Section: Discussionmentioning
confidence: 99%
“…Táplálkozásuk és egyéb élőhelyhasználati aktivitásuk során kifejtett hatásaikat együttesen vadhatásnak nevezi a szakirodalom (vö. Velamazán et al 2018, Ramirez et al 2019, Nopp-Mayr et al 2020. Az élőhelyek szempontjából a vadhatást általában negatív előjellel (fékező, akadályozó, destruktív vonatkozásban) értelmezzük, de kisebb számban kedvező ökológiai hatásokra -így például magterjesztésben betöltött pozitív szerepre (Schmidt et al 2004, Mráz et al 2016) -is találunk példát.…”
Section: Bevezetésunclassified